Seismic Behaviour of a Single Span Historical Masonry Bridge - Ozmen, Alper; Sayin, Erkut (Mouloud Mammeri Univ Tizi-Ouzou, 2023)
A major portion of the cultural heritage consists of old structures that are susceptible to earthquakes. These structures are prone to significant damage from natural disasters, particularly earthquakes. This study's primary goal is to assess the historical masonry bridge's seismic response to strong far-fault ground motions (FFGM) and near-fault ground motions (NFGM). The historical Sultan Suyu Masonry Bridge is used as a case study in this study. It was created with three-dimensional finite element software. The time history response of the bridge model is contrasted with one another in terms of stresses and displacements produced for FFGM and NFGM. The assessments take into account the FFGM and NFGM of the 1999 Duzce, 1999 Kocaeli, and 1992 Erzincan earthquakes, which had nearly equal peak ground accelerations. The results show that FFGM is equally significant as NFGM and that FFGM could be used in conjunction with NFGM to further evaluation of historical masonry arch bridges.
Keywords: Masonry arch bridge; Finite element model; Near and far-fault ground motion; Seismic behavior